Timing and cost of scaling up surgical services in low-income and middle-income countries from 2012 to 2030: a modelling study - Dr. Stéphane Verguet, PhD; Blake C Alkire, MD; Stephen W Bickler, MD; Jeremy A Lauer, PhD; Tarsicio Uribe-Leitz, MD; George Molina, MD; Thomas G Weiser, MD; Gavin Yamey, MD; Mark G Shrime, MD (Elsevier, 2015)
Background: Given the large burden of surgical conditions and the crosscutting nature of surgery, scale-up of basic surgical services is crucial to health-system strengthening. The Lancet Commission on Global Surgery proposed that, to meet populations' needs, countries should achieve 5000 major operations per 100 000 population per year. We modelled the possible scale-up of surgical services in 88 low-income and middle-income countries with a population greater than 1 million from 2012 to 2030 at various rates and quantified the associated costs. Methods: Major surgery includes any intervention within an operating room involving tissue manipulation and anaesthesia. We used estimates for the number of major operations achieved per country annually and the number of operating rooms per region, and data from Mongolia and Mexico for trends in the number of operations. Unit costs included a cost per operation, proxied by caesarean section cost estimates; hospital construction data were used to estimate cost per operating room construction. We determined the year by which each country would achieve the Commission's target. We modelled three scenarios for the scale-up rate: actual rates (5·1% per year) and two "aspirational" rates, the rates achieved by Mongolia (8·9% annual) and Mexico (22·5% annual). We subsequently estimated the associated costs. Findings: About half of the 88 countries would achieve the target by 2030 at actual rates of improvements, with up to two-thirds if the rate were increased to Mongolian rates. We estimate the total costs of achieving scale-up at US$300-420 billion (95% UI 190-600 billion) over 2012-30, which represents 4-8% of total annual health expenditures among low-income and lower middle-income countries and 1% among upper middle-income countries. Interpretation: Scale-up of surgical services will not reach the target of 5000 operations per 100 000 by 2030 in about half of low-income and middle-income countries without increased funding, which countries and the international community must seek to achieve expansion of quality surgical services. Funding: None.